Answer :

Let the weight of the first piece of pizza be x g.

The first piece is 7g lighter than the second piece.

∴ The weight of the second piece of pizza = (x + 7) g.

The first piece is 4g heavier than the third piece.

∴ The weight of the third piece of pizza = (x – 4) g.

The total weight of the pizza = 300g.

According to the given condition,

x + (x + 7) + (x – 4) = 300

⇒ x + x + 7 + x – 4 = 300

3x + 3 = 300

⇒ 3x = 300 – 3 (Transposing 3 to RHS)

3x = 297

⇒ x = (Transposing 3 to RHS)

x = 99

The weight of the first piece = x = 99g.

The weight of the second piece = x + 7 = 99 + 7 = 106g.

The weight of the third piece = x – 4 = 99 – 4 = 95g.

∴ The weights of the three pieces of pizza are 95g, 99g and 106g.

Rate this question :

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics